2018
DOI: 10.1504/ejim.2018.10014753
|View full text |Cite
|
Sign up to set email alerts
|

New strategies to measure and strengthen the social role of business incubators: their application to a Spanish region

Abstract: Business incubators can be defined as a service meant to promote entrepreneurship and firm creation, especially within sectors characterised by a high innovative content. The present paper takes as its starting point a review of previous studies dedicated to the profitability of investments in general, and particularly to that of business incubators, seeking to propose an own method which can make it possible to measure both the economic and the social profitability of business incubators. The subsequent appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Hussain et al, (2018, p. 124) have shown that the leader's 'ethicality' is one of the most important sources for organisational change, while Sanz Ponce, Peris Cancio, and Esc amez S anchez (2018) have cogently argued for the need to introduce human development and capabilities as an alternative notion which transcends classical economic patterns of thinking, merely based on Gross Domestic Product. Gonz alez-Ramos, Donate, and Guadamillas (2018), Llanos-Contreras & Alonso-dos-Santos (2018), Kallmuenzer, Hora, and Peters (2018), and Sentana, Gonzalez, Gasco, and Llopis (2018) have also contributed to highlighting the importance of ethical notions like social sensitivity, socioemotional priorities, socioemotional wealth and social profitability in small business and entrepreneurial decisions. Similarly, Vuorio, Puumalainen, and Fellnhofer (2018) have argued that sustainability is becoming a main driver of entrepreneurial intentions.…”
Section: Methodsmentioning
confidence: 99%
“…Hussain et al, (2018, p. 124) have shown that the leader's 'ethicality' is one of the most important sources for organisational change, while Sanz Ponce, Peris Cancio, and Esc amez S anchez (2018) have cogently argued for the need to introduce human development and capabilities as an alternative notion which transcends classical economic patterns of thinking, merely based on Gross Domestic Product. Gonz alez-Ramos, Donate, and Guadamillas (2018), Llanos-Contreras & Alonso-dos-Santos (2018), Kallmuenzer, Hora, and Peters (2018), and Sentana, Gonzalez, Gasco, and Llopis (2018) have also contributed to highlighting the importance of ethical notions like social sensitivity, socioemotional priorities, socioemotional wealth and social profitability in small business and entrepreneurial decisions. Similarly, Vuorio, Puumalainen, and Fellnhofer (2018) have argued that sustainability is becoming a main driver of entrepreneurial intentions.…”
Section: Methodsmentioning
confidence: 99%